Keeping the score: Outreach services and collaboration for academic music libraries in financially straitened times. Issue 6 (10th August 2015) - Kostagiolas, Petros A.; Lavranos, Charilaos; Martzoukou, Konstantina; Papadatos, Joseph
Abstract : Purpose: – The purpose of this paper is to study the role of academic music libraries in financially straitened times. The academic music library aims to cover the information needs of the academic community; yet the unique nature of music information also allows academic libraries to develop services for a broad spectrum of different user groups. Design/methodology/approach: – The theoretical analysis is supported by empirical evidence from a nationwide survey in Greece. The survey was carried out from July to September 2013 and presents results from interviews with the directors of all academic music libraries in Greece. Findings: – The results suggest that the period of economic crisis is also a period of challenges and innovation for music libraries which calls them to redefine policies and priorities, and further consider the needs and expectations of wider audiences, i.e. musicians outside the academic community. The financial downturn can be seen as an opportunity for restructuring the academic music libraries and for the development of a wider framework of operation which calls for an outreach strategy and cooperation with external music associations and organizations. Originality/value: – It is one of the very few studies providing theoretical and empirical evidence linking academic music libraries to musicians and the significance of collaborative partnerships.